SNSs Engagement and Consumer Purchase Intention toward Foreign Brand Products: The Roles of Foreign Brand Product Judgment and Consumer Ethnocentrism - Dang Van , Thac; Do Thi Hai , Ninh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The purpose of this study is to investigate the relationship between social networking sites (SNSs) engagement and consumers’ intention to purchase foreign brand products, with the mediating role of foreign brand product judgment and the moderating role of consumer ethnocentrism. Using a sample data of 482 consumers on SNSs from two metropolitans in southern of Vietnam. SPSS 24 and Amos 20 were applied to do analysis and provide the results for this study. Empirical results show that SNSs engagement does not have a direct influence on purchase intention while foreign brand product judgment has a positive mediating effect on the link between SNSs engagement and purchase intention. By contrast, consumer ethnocentrism has a negative influence on purchase intention toward foreign brand products, and it also negatively moderates the relationship between SNSs engagement and purchase intention. The results of this study provide implications for both researchers and business managers in understanding and making decisions regarding consumer behavior toward foreign brand products on SNSs environment.
Keywords: SNSs engagement; Purchase intention; Product judgment; Consumer ethonocentrism; Foreign brand products